1997
DOI: 10.1021/tx970099w
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Conjugation of Bay- and Fjord-Region Diol Epoxides of Polycyclic Aromatic Hydrocarbons by Glutathione Transferases M1-1 and P1-1

Abstract: Metabolism of polycyclic aromatic hydrocarbons in mammalian cells results in the formation of vicinal diol epoxides considered as ultimate carcinogens if the oxirane ring is located in a bay- or fjord-region of the parent compound. In the present study, individual stereoisomers of the bay-region diol epoxides of chrysene, dibenz[a,h]anthracene, and benzo[a]pyrene as well as of the fjord-region diol epoxides of benzo[c]phenanthrene, benzo[c]chrysene, and benzo[g]-chrysene have been incubated with GSH in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
2
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 30 publications
(58 reference statements)
9
88
2
5
Order By: Relevance
“…Based on the position of the epoxide ring, PAH diol epoxides can be classified either as bay region or fjord region [43]. GSTP1 demonstrates appreciable activity toward both bay-and fjord-region diol epoxides, but shows a preference for the anti-diastereomers [44], which are more carcinogenic [45]. GSTP1 variants at codon 105 also have variable catalytic efficiencies toward PAH, which vary by the isomeric class of the molecule [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the position of the epoxide ring, PAH diol epoxides can be classified either as bay region or fjord region [43]. GSTP1 demonstrates appreciable activity toward both bay-and fjord-region diol epoxides, but shows a preference for the anti-diastereomers [44], which are more carcinogenic [45]. GSTP1 variants at codon 105 also have variable catalytic efficiencies toward PAH, which vary by the isomeric class of the molecule [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic efficiency of different GSTs (isoenzymes of Alpha, Mu, and Pi have been tested so far) with respect to a number of DE diastereomers and their corresponding enantiomers varies markedly. In addition, certain isoenzymes, for example, those belonging to class Pi, exhibit an exclusive preference for the DE enantiomers with R-absolute configuration at the benzylic arene carbon (of the DE isomers identified as ultimate carcinogens), whereas others (e.g., class Alpha and Mu isoenzymes) are less selective (Sundberg et al 1997).…”
Section: Pah Exposure In Humansmentioning
confidence: 99%
“…Studies of the conjugation of the most metabolically relevant (+)-syn and (−)-anti-DBPDE metabolites indicated that the hGSTP1-1 isozyme exhibited appreciable activity toward (−)-anti and (+)-syn enantiomers of DBP diol epoxides, with preference for conjugation of the (−)-anti-diastereoisomers [20,21]. More recent studies demonstrated that purified hGSTA1-1 exhibits at least an order of magnitude more efficient activity for the conjugation of (−)-anti-DBPDE compared to hGSTM1-1 and hGSTP1-1 [22].…”
Section: Introductionmentioning
confidence: 99%
“…The (−)-anti-DBPDE stereoisomer was responsible for the majority of DBPDE-DNA adducts, and was produced as a greater proportion of the total metabolites by hCYP1B1 as compared to hCYP1A1 [17,18]. Interestingly, however, activation via hCYP1A1-mediated metabolism of DBP elicited stronger cytotoxic effects [19], possibly due to polar DNA adducts of metabolites produced only in cells expressing hCYP1A1.Studies of the conjugation of the most metabolically relevant (+)-syn and (−)-anti-DBPDE metabolites indicated that the hGSTP1-1 isozyme exhibited appreciable activity toward (−)-anti and (+)-syn enantiomers of DBP diol epoxides, with preference for conjugation of the (−)-anti-diastereoisomers [20,21]. More recent studies demonstrated that purified hGSTA1-1 exhibits at least an order of magnitude more efficient activity for the conjugation of (−)-anti-DBPDE compared to hGSTM1-1 and hGSTP1-1 [22].…”
mentioning
confidence: 99%